Lords of the Sky : Fighter Pilots and Air Combat, from the Red Baron to the F-16 - Hampton, Dan (New York William Morrow, 2014)
"By the USAF F-16 legend behind the bestselling memoir Viper Pilot, this is the first comprehensive history of fighter pilots and air combat--a unique, riveting look at the aces of the sky, their machines, their most daring missions, and the epic conflicts they shaped, from the trailblazing aviators of World War I to today's supersonic jets. Lords of the Sky is a thrilling history of the fighter pilot, masterfully
Include Index, Bibliography, Glossary, Maps and Illustration
Keywords: Fighter pilots -- Fighter planes -- Air warfare